The physical characteristics of elite and qualified female canoe paddlers in China - Gao, X.; Guo, P.; Kong, X.; Rusanova, O.; Diachenko, A.; Kudria, M. (SportMont, 2021)
The main objective of this research was to determine the physical characteristics of elite and qualified female canoe paddlers in China. Seventeen paddlers, leading athletes of Shandong and Jiangxi provinces, winners, prize winners and participants of the final races of the China Canoe Racing Championship took part (age 21±2; height=167±2 cm; mass 53.5±1.1 kg). The article shows that female canoe paddlers have superior aerobic and anaerobic qualities and have reported maximal oxygen consumptions of around 56.8 ml·kg-1·min-1 and lactate values of around 12.01 mmoll-1 during laboratory testing. The range of individual differences of as in the range of 107.00-116.00 for elite female canoe paddlers, 99.5-103.5 for female canoe paddlers (province team) and 85.0-91.0 for female canoe paddlers (reserve team) (p<0.05). The research has shown that all physiological characteristics are reduced in relation to the model character-istics of sports (competitions), similar in duration and intensity of work in the canoe. There is no normative basis for outstanding operability in the process of modelling competitive activity and in implementing the components of the energy supply structure.